INFORMATION WEAPONS AS A TOOL OF INFORMATION WARFARE - Khoroshko, Volodymyr; Khokhlachova, Yuliia; Pirtskhalava, Tina; Ivanchenko, Ihor (Ukrainian Information Security Research Journal, 2022)
Information weapons are a new evolutionary step on the way to the development of the latest types of weapons. Such a weapon has specific and characteristic features only for it. In the modern conditions of Russia's military aggression, the armed struggle has acquired the characteristics of not only an information war. Its emphasis shifted towards the implementation of information technologies. At the same time, information and psychological operations, actions, actions and information weapons are gaining more and more importance in the achievement of political and military goals, the underestimation of the capabilities of which in the modern information war can become fatal during the further aggravation of the military and political situation. This is confirmed by the hostilities currently taking place in Ukraine.In a modern war, it is impossible to achieve the set goals without the constant implementation of measures of information warfare. Therefore, experts single out information weapons as an independent type of weapon, which is considered as a means of information warfare.Information warfare and influence can be carried out in the political, economic, defense, scientific and technical and other spheres by: influencing elements of information and telecommunication systems with the aim of destroying elements of the infrastructure of state and military administration, interception and processing of open information circulating in information systems and published in mass media; unauthorized access to information resources and their subsequent rearrangement, destruction or embezzlement; interception and decryption of information flows transmitted by communication channels, side emissions or received through the use of special technical means of information interception; formation and dissemination of information channels of the enemy or global networks of disinformation with the aim of influencing the evaluations, intentions and orientation of people, groups of people, society as a whole and the military and political leadership of the state.Information warfare is the spread of certain ideas, views or ideology, and is a means of certain politics. The global tool for its implementation is mass media and various communications.The article also discusses the theory of information warfare in the political sphere, it should be considered that it takes place at the strategic, operational and tactical levels.Mainly, the highest political elite of the state operates at the strategic level, and the information units of the political path operate at the operational and tactical levels.